Intimate partner violence against women: Operationalized Psychodynamic Diagnosis (OPD-2) - Both, Luciane Maria (PLoS One, 2020)
INTRODUCTION: Intimate partner violence against women is one of the most common forms of violence. Different research fields are trying to understand the cycle of violence, such as the psychological field, to understand how these women's relational patterns and intrapsychic conflict function in the cycle of violence. OBJECTIVE: To investigate the operationalized psychodynamic diagnosis of women victims of domestic violence, exploring the severity and experience of violence, structural functions, dysfunctional interpersonal patterns, and intrapsychic conflicts. METHOD: We conducted a cross-sectional quantitative study using the OPD-2 Clinical Interviews, which were recorded and transcribed. The sample was composed by 56 women victims of domestic violence, mean age 30.07 (SD = ±9.65). Reliability was satisfactory for judges interviews(k>0,6). RESULTS: According to the OPD-2 evaluation, we found that the severity of the violence was associated with the intensity of women's subjective suffering. In the relational pattern, they stay in the relationship, leaving themselves vulnerable; perceive the partner as controlling, aggressive, offensive, and fear abandonment. As a defensive mechanism to relational discomfort and suffering victims anticipate the aggressor's desire, resulting in submissive behavior. The main psychic conflict was the "need for care versus self-sufficiency" (78.6%). And medium was the predominant structure level, in which they presented insecure internal objects, presenting difficulties in emotional regulation and perceiving reality in a distorted way. Hence, they do not recognize their limitations and needs. We found that 78.6% of the cases had some psychiatric disorder: MDD, PTSD. CONCLUSION: This study provides empirical evidence on clinical observations on the psychological functioning of this population and the issues that make up the maintenance of domestic violence against women. The understanding of internalized patterns, structural functions, and motivational tensions are fundamental for the prevention of re-victimization and improving coping mechanisms, as well as promoting greater adherence to treatment.